2005
DOI: 10.1007/s00535-004-1446-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural 5A gene variability of hepatitis C virus (HCV) during a 10-year follow up

Abstract: Our findings showed that the functional domains of NS5A were generally conserved over an interval of 10 years. Quasispecies distribution was variable and distinctly clustered over time during the natural course of HCV infection. These results may contribute to better understanding of HCV natural infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Nonsense mutations in samples from HCV-infected patients have been described [34,36,49], but the structural and functional implications of such mutations detected in vivo are unclear. Most of the nonsense mutations detected were located in the N-terminal region of NS5A (Alpha Helix, Domain I or Low Complexity Sequence I regions of the NS5A); only one was located in the C-terminal region (domain III).…”
Section: Discussionmentioning
confidence: 99%
“…Nonsense mutations in samples from HCV-infected patients have been described [34,36,49], but the structural and functional implications of such mutations detected in vivo are unclear. Most of the nonsense mutations detected were located in the N-terminal region of NS5A (Alpha Helix, Domain I or Low Complexity Sequence I regions of the NS5A); only one was located in the C-terminal region (domain III).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al (34) found that the functional domain of NS5A remained conserved over an interval of 10 years of follow-up. Similarly, other studies showed that, in patients without HCC, the NS5A-PKR sequences did not change considerably during the natural course of liver disease (35), and the variable quasispecies structure of NS5A remains largely stable, independent of the degree of liver disease (36).…”
Section: Discussionmentioning
confidence: 99%
“…5 0 UTR is a more conserved part of HCV genome, which helped in evolutionary studies and genotyping [11,12].…”
Section: History and Structure Of Hepatitis C Virusmentioning
confidence: 99%